PERBEDAAN OUTCOME KLINIS ANTARA PASIEN STROKE ISKEMIK DENGAN FAKTOR RISIKO DIABETES MELITUS TIPE 2 TERKONTROL DAN DIABETES MELITUS TIPE 2 TIDAK TERKONTROL BERDASARKAN NILAI SKALA STROKE GADJAH MADA (SSGM) SAAT MASUK RUMAH SAKIT - , PUTRI CLAUDYA O ([Yogyakarta] : Universitas Gadjah Mada, 2014)
s Background: Stroke i the second most common cause of death throughout the world. Ischemic or infark stroke is a functional impairment of the brain as a result of brainâs blood flow disorder, either due to occlusion or decreased perfusion. Ischemic stroke accounts for 80% of stroke prevalence. About 20% of stroke patients have diabetes mellitus (DM) as a risk factor. DM can increase the risk of stroke twice, especially the ischemic stroke, and has proven as a one of strokeâs bad outcome predictor. Type 2 DM is related to lifestyle and can be controlled, either by diabeticâs medication, lifestyle modification, or both of them. Controlling the type 2 diabetes mellitus and keeping low levels of the blood sugar can make a better strokeâs clinical outcome. know Objective: To that the average values of SSGM score at hospital admission is higher for ischemic stroke patients with controlled type 2 DM than ischemic stroke patients with uncontrolled type 2 DM as a strokeâs risk factor. Methodology: This study was an observational study with cross-sectional design. The datas were taken retrospectivelly from the medical records of in-patients ischemic stroke in neurological and stroke unit. The medical records of stroke patients was selected subsequently based on inclusion and exclusion criteria. There were 94 patientâs datas obtained. Patientâs datas such as random blood glucose level, age, sex, time of arrival at the hospital, HbA1c level, total cholesterol level, HDL cholesterol level, LDL cholesterol level, triglycerides level, hipertension history, history of previous TIA, history of previous heart disease, smoking history, history of previous stroke, and the SSGM score at hospital admission were recorded. These data, then, were grouped into binominal datas, except the SSGM score at hospital admission. apiro Analysis: Kormogolov-Smirnov test and Sh -Wilk test were used for data normality testing. Levene test was used for data homogeneity testing. Two sample independent ttest and Mann-Whitney test were used for hypothesis testing. was Results: There a higher average SSGM score at hospital admission in ischemic stroke patients with controlled type 2 DM than ischemic stroke patients with uncontrolled type 2 DM. The difference value between both group was 1,012 and this result was significant (p=0,002). Analysis of the average SSGM score at hospital admission on confounding variables showed no significant results. It consist of age (p=0,852), gender status (p=0,937), time of arrival (p=0,347), HbA1C level (p =0,346), total cholesterol level (p =0,905), LDL cholesterol level (p=0,482), HDL cholesterol level (p=0,435), triglyceride level (p=0,69), history of previous hypertension (p =0,565), history of previous TIA (p=0,0565), history of previous heart disease (p=0,787), history of smoking (p=0,598), and history of previous stroke (p=0,511). Conclusion: There is a higher average of SSGM score at hospital admission in ischemic stroke patients with controlled type 2 DM compared to ischemic stroke patients with uncontrolled type 2 DM. This result shows a better clinical outcome of ischemic stroke patient with controlled type 2 DM than ischemic stroke patient with uncontrolled type 2 DM as a strokeâs risk factor.